Benford's Law and County-Level Votes in US Presidential Elections. Issue 2 (3rd April 2022) - Groharing, Brooks; McCune, David
Abstract : In the aftermath of the 2020 US Presidential election, the argument was raised that because Joseph Biden's county vote totals in Pennsylvania do not follow Benford's law but Donald Trump's do, Democratic voter fraud occurred in Pennsylvania. We use US recent presidential election data to investigate whether this argument holds water. We use statistical tools such as chi squared goodness-of-fit tests and hypothesis tests for proportions, which are commonly used in Benford settings.